Antibacterial Activity of Malaleuca Leucadendron Linn Essential Oil from North Central Timor Against Escherichia coli and Staphylococus Aureus - Kolo, Sefrinus M.D.; Mere, Janrigo Klaumegio; Klau, Emirensiana H.; Obenu, Noviana M. (Indonesian Journal of Chemical Research, 2024)
The eucalyptus plant (Melaleuca leucadendron Linn) is one of the essential oil production plants in the world. The plant has been widely used as an antiseptic and also for relieving colds, sore throat, and infections. This study aims to identify the whole essential oil compounds of this plant using GC-MS and test the antibacterial activity of the essential oil using the disc diffusion method. Based on the results of the GC-MS analysis of the essential oil content obtained by steam distillation and antibacterial test using discs diffusion method to Escherichia coli and Staphylococcus aureus, yielded 81 compound peaks with antibacterial activity analysis results classified as relatively very strong at 5 different concentrations. The results of the best antibacterial activity test were indicated by the diameter of the inhibition zone 26.42 ± 0.97 mm for Escherichia coli while Staphylococcus aureus 23.43 ± 2.09 mm at a concentration of 100%. The study of antibacterial compounds based on the 81-peak GC-MS analysis found that 8 compounds have been reported as antibacterial. These compounds belong to the terpenes group with total percentages of eucalyptol 20.97 %, terpineol 11.74 %, β-pinene 6.24%, 3-carene 1.95%, caryophyllene 4.96 %, (z)-geraniol 0.10%, farnesol 0.10%, and eugenol 0.18% respectively